Diseño e implementación de un sistema de reconocimiento automáticodel número de placa de un vehículo para control de acceso y seguridad de la Universidad Técnica de Machala - Siguenza Encarnación, Janneth Alexandra (2014)
At the Technical University of Machala circulating vehicles in which teachers, students, employees attending perform their professional and educational activities are moved daily; and there was no control on the access of different vehicles that regularly transport, this allowed any private vehicles can access the institution without being registered, this inducing distrust and uncertainty for those who are working in the institution .